Imipramine is an orally active drug against both antimony sensitive and resistant Leishmania donovani clinical isolates in experimental infection. - Sandip Mukherjee; Budhaditya Mukherjee; Rupkatha Mukhopadhyay; Kshudiram Naskar; Shyam Sundar; Jean Claude Dujardin; Anjan Kumar Das; Syamal Roy (Public Library of Science (PLoS), 2012)
BACKGROUND: In an endeavor to find an orally active and affordable antileishmanial drug, we tested the efficacy of a cationic amphiphilic drug, imipramine, commonly used for the treatment of depression in humans. The only available orally active antileishmanial drug is miltefosine with long half life and teratogenic potential limits patient compliance. Thus there is a genuine need for an orally active antileishmanial drug. Previously it was shown that imipramine, a tricyclic antidepressant alters the protonmotive force in promastigotes, but its in vivo efficacy was not reported. METHODOLOGY/PRINCIPAL FINDINGS: Here we show that the drug is highly active against antimony sensitive and resistant Leishmania donovani in both promastigotes and intracellular amastigotes and in LD infected hamster model. The drug was found to decrease the mitochondrial transmembrane potential of Leishmania donovani (LD) promastigotes and purified amastigotes after 8 h of treatment, whereas miltefosine effected only a marginal change even after 24 h. The drug restores defective antigen presenting ability of the parasitized macrophages. The status of the host protective factors TNF α, IFN γ and iNOS activity increased with the concomitant decrease in IL 10 and TGF β level in imipramine treated infected hamsters and evolution of matured sterile hepatic granuloma. The 10-day therapeutic window as a monotherapy, showing about 90% clearance of organ parasites in infected hamsters regardless of their SSG sensitivity. CONCLUSIONS: This study showed that imipramine possibly qualifies for a new use of an old drug and can be used as an effective orally active drug for the treatment of Kala-azar.